Transformasi Kesadaran Halal di Era Media Sosial: Studi Netnografi Pada Konten Instagram di Indonesia - MUTIARA SALSABIILAA; Putri Ayushifa Kurniati; Maulana Syarif Hidayatullah (At-Taradhi Jurnal Studi Ekonomi, 2026)
Amid Indonesia's ambition to become a global halal hub, this study examines how halal awareness among Indonesian Muslims is transformed in the digital era through Instagram, addressing a gap in prior research that has treated social media's role in this process largely descriptively. Using a qualitative netnographic approach, the study traces interactions, narratives, and digital practices on the @halalcorner account, analyzing four high-engagement posts through the combined lenses of the Theory of Planned Behavior and Uses and Gratifications Theory. The findings show that Instagram functions not only as a communication medium but also as a space for digital da'wah, public education, and halal identity formation, with halal awareness unfolding across four stages — knowledge, attitude, practice, and lifestyle. Educational content, clarification of halal-related controversies, and two-way communication between account administrators and audiences strengthen Muslim consumers' halal literacy, while younger generations, digital communities, and influencers expand the halal value network and accelerate the modern internalization of sharia principles. The study confirms Instagram's significant role in shaping halal awareness amid Indonesia's digital culture, extending TPB and Uses and Gratifications Theory to naturally occurring audience discourse.